The Explosion Severity of Biogas(CH4-CO2)/Air Mixtures in a Closed Vessel - Nur Aqidah, Muhammad Harinder Khan; Siti Zubaidah, Sulaiman; Izirwan, Izhab; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Rafiziana, Md Kasmani; Sarina, Sulaiman (2018)
Biogas which consists of methane (CH4) and carbon dioxide (CO2) could explode when diluted to a certain degree with air in the presence of ignition source. The maximum explosion overpressure (Pmax), the maximum rate of pressure rise (dP/dt)max, flammability limits, and deflagration index are the most important explosion severities parameters to characterize the risk of explosion. In this research paper, the effect of equivalence ratio (ER) of biogas/air mixtures and the effect of CO2 concentrations presence in biogas were studied in a 20 L spherical vessel. The values of Pmax and (dP/dt)max of biogas/air mixtures were more severe at ER 1.2. At various CO2 content, Pmax and (dP/dt)max of biogas/air mixtures were the least affected at 45% vol/vol of CO2. On the other hand, deflagration index (KG) of biogas/air mixtures trend was the most severe at 35% vol/vol of CO2 content despite the lowest Pmax and (dP/dt)max at 45% vol/vol of CO2 content. The lowest values in Pmax and (dP/dt)max were due to the diffusivity properties of CH4 that had surpassed the CO2 suppression effect. Furthermore, the presence of CO2 in biogas/air mixtures had increased the upper flammability limit and lower flammability limit of biogas.